2010
DOI: 10.1021/jp109107t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the CN + CS2 and CN + SO2 Reactions

Abstract: Diode infrared laser absorption spectroscopy was used to measure the rate constant (k(1)) of the CN + CS(2) reaction for the first time. k(1) was determined to be substantially pressure dependent with a value k(1) = (7.1 ± 0.2 to 41.9 ± 2.9) × 10(-12) cm(3) molecule(-1) s(-1) over 2-40 Torr at 298 K. The potential energy surface (PES) of the reaction was calculated using an ab initio method at B3LYP/6-311++G(d, p)//CCSD(T)/6-311++G(d, p) level of theory. Both experimental and computational results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Due to the low activation energy of 3.0 kcal/mol, this reaction could take place easily, even in a low temperature region, which well explains the absence of −CN species and the enhancement of the −NCO species generation in the whole temperature range of 150–350 °C, as presented in Figure b. The calculation results about the reaction of −CN + SO 2 → −NCO + SO was similar to that reported by Hershberger et al…”
Section: Resultssupporting
confidence: 85%
“…Due to the low activation energy of 3.0 kcal/mol, this reaction could take place easily, even in a low temperature region, which well explains the absence of −CN species and the enhancement of the −NCO species generation in the whole temperature range of 150–350 °C, as presented in Figure b. The calculation results about the reaction of −CN + SO 2 → −NCO + SO was similar to that reported by Hershberger et al…”
Section: Resultssupporting
confidence: 85%
“…This would lead to an observed decay rate for [CN] vs time that is slower than would be expected from the CN + O 2 reaction alone, resulting in an erroneously small value of the CN + O 2 rate constant. A similar issue was raised in our recent study of CN + SO 2 kinetics, in which we found essentially no reaction with k ≤ 3.1 × 10 −14 cm 3 molecule −1 s −1 , 25 in contrast to an earlier literature value of 4.4 × 10 −12 cm 3 molecule −1 s −1 . 26 Is it possible that O atom formation (possibly via SO 2 multiphoton dissociation or reaction of CN with trace O 2 ) followed by the O + ICN reaction resulted in regeneration of CN radicals, and therefore led to an erroneously small value for the CN + SO 2 rate constant?…”
Section: Introductionsupporting
confidence: 64%
“…CN reactions with a variety of molecules have been previously studied, including both saturated and unsaturated hydrocarbons [1][2][3][4][5][6][7], O 2 [1,[8][9][10][11][12][13][14][15][16], NO [15,17], and NO 2 [16,17]. Past work in our laboratory has included study of CN reactions with O 2 [18,19], NO 2 [20], OCS [21], CS 2 [22], SO 2 [22], and HCNO [23,24]. To date, however, there is no literature on the kinetics of CN reactions with alcohols.…”
Section: Introductionmentioning
confidence: 99%